Program Intervensi Narimo Ing Pandum dalam Meningkatkan Penerimaan Diri ADHA di Kota Yogyakarta - Hanifa, Dea Aurellia; Hayatun Najah, Desita Amalia; Syakila, Ghania Bilqistiyani; Simatupang, Jeremia (Suksma: Jurnal Psikologi Universitas Sanata Dharma, 2023)
According to the Ministry of Health, around 1.7 million children under the age of 14 globally are living with HIV. The condition of physical hardship and social rejection of ADHA makes ADHA have a negative perception that then affects his acceptance. This study aimed to evaluate the effect of the Narimo Ing Pandum intervention program in increasing self-acceptance among children with HIV. In this study, a total of 9 children with HIV aged 7 to 15 years were recruited. The study method used is experimental research design of one group pretest-posttest, and data analysis techniques using t-test statistical analysis techniques. The results showed that the levels of self-acceptance weren’t significantly different before and after the intervention.